2020
DOI: 10.1093/jrr/rraa054
|View full text |Cite
|
Sign up to set email alerts
|

Positional repeatability and variation in internal and external markers during volumetric-modulated arc therapy under end-exhalation breath-hold conditions for pancreatic cancer patients

Abstract: The purpose of this study was to assess the positional repeatability of internal and external markers among multiple breath-hold (BH) sessions and evaluate the positional variation of these markers within BH sessions for volumetric-modulated arc therapy (VMAT) for pancreatic cancer patients. A total of 13 consecutive pancreatic cancer patients with an internal marker were enrolled. Single full-arc coplanar VMAT was delivered under end-exhalation BH conditions while monitoring the internal marker with kilovolta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…With respect to rotation, the standard deviation exceeded 3° for 6% of the entire dataset, regardless of the axis. This study also observed inter‐observer variability, consistent with findings from previous studies 3,8,9,17–19 . These findings emphasize the need for auto‐matching techniques to minimize inter‐observer variability and achieve consistent soft‐tissue matching.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…With respect to rotation, the standard deviation exceeded 3° for 6% of the entire dataset, regardless of the axis. This study also observed inter‐observer variability, consistent with findings from previous studies 3,8,9,17–19 . These findings emphasize the need for auto‐matching techniques to minimize inter‐observer variability and achieve consistent soft‐tissue matching.…”
Section: Discussionsupporting
confidence: 90%
“…However, soft‐tissue matching faces several difficulties. Previous studies have consistently identified inter‐ and intra‐observer variability as great issues in soft‐tissue matching 3,8,9 . Hirose et al emphasized the importance of considering inter‐observer variability when determining the clinical target volume for PTV margins 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). Furthermore, VISICOIL was monitored to observe if it was within 2 mm during beam delivery, and when it exceeded that range, CBCT was performed again [ 13 ]. For the patients in Protocol B, backup plans were generated using the same procedure as Protocol A in case VISICOIL could not be recognized during irradiation.…”
Section: Methodsmentioning
confidence: 99%
“…There are many reports on internal errors in external radiation therapy for LAPC, 17 , 18 , 19 , 20 and many problems need to be solved. It has been pointed out that changes in GI tract density are more affected by particle therapy.…”
Section: Discussionmentioning
confidence: 99%